Next‐generation sequencing in residual liquid‐based cytology specimens for cancer genome analysis. Issue 11 (8th June 2020) - Yamaguchi, Tomomi; Akahane, Toshiaki; Harada, Ohi; Kato, Yasutaka; Aimono, Eriko; Takei, Hidehiro; Tasaki, Takashi; Noguchi, Hirotsugu; Nishihara, Hiroshi; Kamata, Hajime; Tanimoto, Akihide
Abstract: Background: Cancer genome profiling of cytology specimens using next‐generation sequencing (NGS) requires adequate and good‐quality DNA. Genomic examination of cytology samples was conventionally performed on cell block (CB) or smear specimens than on residual liquid‐based cytology (LBC) specimens, which are high‐quality DNA sources even after long‐term storage. Methods: We estimated tumor fractions of 37 residual LBC specimens, including 30 fine needle aspiration (FNA) samples from the thyroid (12 papillary thyroid carcinomas and two malignant lymphomas), lymph node (13 metastatic carcinomas and one malignant lymphoma), and breast cancer (one phyllodes tumor and one invasive ductal carcinoma), two pancreatic carcinoma samples, and five liquid (ascites, pleural effusion, and cerebrospinal fluid) samples. The DNA was extracted from all samples and subjected to NGS using a customized cancer gene panel comprising 28 cancer‐related genes. Results: NGS analysis revealed somatic mutations corresponding to pathological diagnosis with adequate variant allele frequency (VAF) in 24 LBC specimens, which had significantly higher tumor fraction (72.5% ± 4.9%). Ten cases, including the five fluid samples, had very small tumor fractions (7.5% ± 2.3%) to obtain sufficient VAF. Other two samples had high tumor fractions but showed very low VAF, indicating the presence of fusion genes. The remaining one sample yielded no DNA recovery. Conclusion: The residual LBC specimens collected by FNA from the thyroid gland and lymph node were verified to carry high tumor fraction and could serve as an alternate source for molecular testing to screen and diagnose cancers without the use of CB or smears.